2015
DOI: 10.1007/s10755-015-9343-6
|View full text |Cite
|
Sign up to set email alerts
|

When Developmental Education is Optional, What Will Students Do? A Preliminary Analysis of Survey Data on Student Course Enrollment Decisions in an Environment of Increased Choice

Abstract: Historically, college students needing additional academic preparation have been assigned to developmental/remedial courses. In 2013 Florida took a drastic departure from this model by passing Senate Bill 1720, which prohibited institutions from requiring placement tests and made developmental education optional for many students, regardless of prior academic preparation. For this pilot study we conducted a survey at two colleges in the Florida College System to begin to understand the kinds of courses student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…Of our sample, 91.5% enrolled in English Composition 1 and 54.8% enrolled in Intermediate Algebra. The low math course-taking rate aligns with previous research that given the option, students may choose to enroll in developmental math or delay enrollment in any math course (Park, Woods, Hu, Bertrand Jones, & Tandberg, 2017;Park et al, 2016;.…”
Section: Data and Samplesupporting
confidence: 75%
“…Of our sample, 91.5% enrolled in English Composition 1 and 54.8% enrolled in Intermediate Algebra. The low math course-taking rate aligns with previous research that given the option, students may choose to enroll in developmental math or delay enrollment in any math course (Park, Woods, Hu, Bertrand Jones, & Tandberg, 2017;Park et al, 2016;.…”
Section: Data and Samplesupporting
confidence: 75%
“…It is not surprising that 46% to 48% of underprepared students chose to enroll in the gateway English course now that they have this option. Previous research has documented that under the recent Florida DE reform, students made enrollment choices based in large part on cost and time to degree (Park, Woods, Richard et al, 2016). It is possible that the students in the current study, particularly those who were closest to the college-ready cut point, opted to bypass DE and enroll in the gateway course for these same reasons.…”
Section: Discussionmentioning
confidence: 97%
“…Exempt students include those who entered a Florida public high school in 2003/04 or later as ninth graders and graduated with a standard high school diploma, as well as active duty military personnel. A survey of student enrollment decisions following the reform indicated that many students did elect to opt out developmental education, even if they were advised to take such courses (Park et al 2016 ). However, some students who felt that they were academically underprepared continued to enroll in developmental education, particularly in math.…”
mentioning
confidence: 99%